Do Developing Countries Benefit from Foreign Direct Investments? - Weshah Razzak; Elmostafa Bentour (Economics and Econometrics Research Institute (EERI), 2012)
In addition to the wide believed positive effects on growth, employment and wages, FDIs are often perceived as sources of funds for development. Developing countries, especially low income and emerging economies, welcome FDIs because of their favorable budgetary implications. All that resulted in increasing global FDIs. We discuss some specification and estimation problems that might affect the estimation of the rate of returns on FDI, and provide new figures for a number of FDI-receiving Arab countries. We compare the results to those of some Asian countries, and discuss the policy implications. There is evidence that Arab countries have, relatively, benefited from their efforts to open their economies, to reform their institutions and to attract FDIs.
Keywords: C13; C14; C21; C23; C26; O24; 330; Rate of return on FDI; estimation and specification problems; panel data